Agile Leadership-Based Principal Leadership: Collaborative Culture Transformation And Its Impact On Improving Teachers' Adaptive Performance In The Era Of Impactful Curriculum - Denny Bhekti Kurnianto; Moh Harun Al Rosid; Budi Santoso (Yayasan Darusssalam Bengkulu, 2026)
This study aims to describe the role of Agile Leadership in enhancing teachers’ adaptive performance in secondary schools through active participation, collaboration, and rapid feedback systems. The study was conducted to address the challenges of implementing the Impactful Curriculum, which requires teachers to act as reflective and innovative learners. This research employed a qualitative approach using a case study design, carried out in a senior high school that applies Agile Leadership principles. Data were collected through in-depth interviews with the principal, teachers, and curriculum development team, observations of leadership practices and teacher collaboration dynamics, as well as document analysis of school policies. Data were analyzed using the interactive model of Miles and Huberman, consisting of data reduction, data display, and conclusion drawing. The findings reveal that the application of Agile Leadership fosters a collaborative and adaptive work environment through reflective forums and cross-subject teams. Teachers’ participation in decision-making nurtures a sense of ownership toward school policies and reduces resistance to change. Moreover, the pedagogical experimentation culture built through the agile approach enhances teachers’ adaptability and innovation, thereby strengthening a sustainable learning culture within the school. These findings highlight the importance of agile, participatory, and reflective leadership in navigating the dynamics of 21st-century education.